PENYULUHAN PEMANFAATAN INTERNET YANG BAIK DAN AMAN BAGI ANAK - Ni Made Sulastri, Herlina, Dewi Rayani, dan Farida Herna Astuti (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
The development of technology in the form of the internet in the online learning period has brought many changes. The internet changes face-to-face learning into online learning, the internaet also makes it easier for children to find school assignments. However, the ability of children to use the internet in a good and safe way is still relatively low, especially for children in Bug-bug village, Lingsar sub-district which is located far from urban areas and the lack of attention from parents in supervising children in using the internet, parents' routines are also an obstacle in supervision of internet use in children. Most children can freely surf in cyberspace and carry out their online activities without supervision. Therefore, counseling activities on the use of the internet that are good and safe for children really need to be done to inform, provide knowledge and provide awareness for children about how to use the internet in a wise way so that in the future their academic abilities and knowledge of the world of education and information will increase. With this community service activity, it is hoped that children will be able to use the internet wisely and be able to provide information to parents about how to support good activities for children in wise and safe internet use from an early age. So the results of this community service activity form a good personality for children who are able to use technology, the internet wisely and can compete intellectually and have good behavior.